2022
DOI: 10.1007/s00262-022-03239-9
|View full text |Cite
|
Sign up to set email alerts
|

Cancer-targeted photoimmunotherapy induces antitumor immunity and can be augmented by anti-PD-1 therapy for durable anticancer responses in an immunologically active murine tumor model

Abstract: The complex immunosuppressive nature of solid tumor microenvironments poses a significant challenge to generating efficacious and durable anticancer responses. Photoimmunotherapy is a cancer treatment strategy by which an antibody is conjugated with a non-toxic light-activatable dye. Following administration of the conjugate and binding to the target tumor, subsequent local laser illumination activates the dye, resulting in highly specific target cell membrane disruption. Here we demonstrate that photoimmunoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…The addition of HMGB1 to human peripheral blood mononuclear cell cultures in vitro markedly stimulated the release of cytokines such as TNF, IL‐1α, IL‐1β, IL‐1RA, IL‐6, IL‐8, CCL3, and CCL4 18 . DCs exposed to photoimmunotherapy‐killed FaDu cells had significantly higher concentrations of inflammatory cytokines, including CCL3 and CCL4 19 . It has been shown that CCR5, a chemokine receptor on naive CD8 + T cells, is upregulated in immunogen‐draining lymph nodes, and these cells are attracted to antigen‐specific DC‐CD4 T cell interaction sites, where cognate chemokines CCL3 and CCL4 are produced 20 .…”
Section: Discussionmentioning
confidence: 99%
“…The addition of HMGB1 to human peripheral blood mononuclear cell cultures in vitro markedly stimulated the release of cytokines such as TNF, IL‐1α, IL‐1β, IL‐1RA, IL‐6, IL‐8, CCL3, and CCL4 18 . DCs exposed to photoimmunotherapy‐killed FaDu cells had significantly higher concentrations of inflammatory cytokines, including CCL3 and CCL4 19 . It has been shown that CCR5, a chemokine receptor on naive CD8 + T cells, is upregulated in immunogen‐draining lymph nodes, and these cells are attracted to antigen‐specific DC‐CD4 T cell interaction sites, where cognate chemokines CCL3 and CCL4 are produced 20 .…”
Section: Discussionmentioning
confidence: 99%
“…One such approach is to recombinantly engineer a SNAP-tag domain into any of the termini of the scFv. This domain, which mimics the human DNA repair enzyme O 6 -alkylguanine-DNA alkyltransferase (hAGT), contains a thiolate nucleophile that can be alkylated by a methylene (on the end of the linker) bearing an O 6 -benzylguanine (BG) leaving group, thus producing homogeneous ADC conjugates with reproducible 1:1 stoichiometry. To date, there have been few examples reported in the literature of promising scFv-based ADCs using SNAP-tag conjugation methodology. , ,, Furthermore, although, to date, click chemistry is known for linker connection chemistry in IgG-based ADCs, to the best of our knowledge, there are no reports of using a click strategy for linker connection to a scFv. This facet features as a novel aspect of the present work in that we have achieved the first click strategy for assembling an scFv-based ADC involving a noncleavable linker, whose characteristics are reviewed below. Our strategy affords a relatively facile means of modular assembly for accessing a library of scFv-based ADC structural variants.…”
Section: Introductionmentioning
confidence: 92%
“…The epidermal growth factor receptor (EGFR) is a member of the transmembrane tyrosine kinase receptor family (HER), comprising an extracellular ligand binding domain (EC), a transmembrane domain (TM), and an intracellular domain with tyrosine function. , EGFR activation starts with ligand binding that triggers dimerization (homo- and/or heterodimerization), which leads to tyrosine kinase domain autophosphorylation. In turn, this activates a cascade of downstream signaling pathways such as the RAS/MAPK, PI3K/Akt, Jak/Stat, and activator-of-transcription 3 (STAT3) pathway, all of which are implicated in the transcriptional regulation of genes involved in cell proliferation, cell survival, migration, and drug resistance. As a result, novel therapeutic strategies in the form of anti-EGFR monoclonal antibodies (mAbs) and tyrosine kinase inhibitors (TKIs) (e.g., gefitinib and erlotinib) have been developed. These therapies work respectively by obstructing EGFR binding with agnostic ligands (mAbs) and by suppressing the intracellular tyrosinase activity through disruption of adenosine-5′-triphosphate (ATP) binding (TKIs). The clinical success of these therapies was demonstrated by the FDA approval of erlotinib (2004) and gefitinib (2015) for the treatment of non-small-cell lung cancer (NSCLC), and cetuximab (approved in 2004) and panitumumab (2006) mAbs for treating colorectal cancer. ,,, However, these (cetuximab and panitumumab) are yet to demonstrate palpable therapeutic benefits, as they only achieve significant therapeutic efficacies when combined with systemic chemotherapy or radiotherapy and TKIs but not when used as monotherapy. Therefore, efforts to mitigate these suboptimal therapeutic effects have paved the way for the development of antibody–drug conjugates (ADCs), a fast-growing type of biotherapeutic with the potential to increase the antitumor activity of an antibody. , These ADCs typically comprise a mAb serving as a vehicle that selectively recognizes cancer cells overexpressing cognate cell surface receptors in comparison to normal cells. Upon recognition through ligand–receptor binding, the mAb enters the cell to specifically deliver the cytotoxic molecule, which subsequently induces cell death in cancer cells but not in normal cells. , …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations